MEK inhibition induced downregulation of MRP1 and MRP3 expression in experimental hepatocellular carcinoma - Lin, Shibo; Hoffmann, Katrin; Xiao, Zhi; Jin, Nan; Galli, Uwe; Mohr, Elvira; Büchler, Markus W.; Schemmer, Peter (Cancer cell international, 2013)
Hepatocellular carcinoma (HCC) exhibits strong intrinsic and acquired drug resistance which is the main obstacle to chemotherapy. Overexpression of ATP binding cassette (ABC) proteins correlates with activation of mitogen activated protein kinase (MAPK) pathway in HCC. Here, we systematically investigated the inhibition of MAPK pathway and its role in regulating HCC cell growth as well as ABC proteins MRP1 and MRP3 expression.